2022
DOI: 10.1111/jocn.16461
|View full text |Cite
|
Sign up to set email alerts
|

Factors preceding occupational distress in emergency nurses: An integrative review

Abstract: Aims and Objectives: This integrative review aimed to synthesise current evidence on the factors that precede and contribute to the occupational distress of emergency nurses.Background: Emergency nurses practice within an environment challenged by demand exceeding capacity, an inability of staffing to meet this demand in addition to limited resources which contribute to form a unique risk to clinician and patient safety.The risk of occupational distress, while demonstrated across specialties, is noted to be hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Clinicians working with patients experiencing mental health crises are at risk of suffering from vicarious or secondary trauma from mental health patients 22,29,30 . Many participants in our study noted that the home lives of their patients are not conducive to healing and could be traumatizing, resulting in repeat admissions.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Clinicians working with patients experiencing mental health crises are at risk of suffering from vicarious or secondary trauma from mental health patients 22,29,30 . Many participants in our study noted that the home lives of their patients are not conducive to healing and could be traumatizing, resulting in repeat admissions.…”
Section: Discussionmentioning
confidence: 84%
“…Clinicians working with patients experiencing mental health crises are at risk of suffering from vicarious or secondary trauma from mental health patients. 22,29,30 Many participants in our study noted that the home lives of their patients are not conducive to healing and could be traumatizing, resulting in repeat admissions. Additionally, triggering life events reported by patients were particularly upsetting T A B L E 3 Clinician-reported self-care activities and resilience supports.…”
Section: Discussionmentioning
confidence: 91%
“…On a similar note, Caulfield et al. (2022) reported that excessive workload in emergency departments led to job distress in emergency nurses, with a negative impact on the quality of patient care and patient safety. According to the sensitive nature of emergency care, senior emergency department managers should take measures to recruit nurses who have the necessary professional capabilities.…”
Section: Discussionmentioning
confidence: 96%
“…The physical and psychological demands of daily life can be quite challenging leading to a range of stressors, such as moral distress. [3][4][5][6] Another fundamental element of nursing that directly impacts well-being is the low level of earnings, which is related to the unsolved problem of social image and acknowledgment. Even if the association between nurses' well-being and earning can be variable according to the different countries, we cannot ignore that the lack of an "economic gain" proportionate to the level of professional responsibilities plays an important role in this issue.…”
Section: Nursingmentioning
confidence: 99%
“…Currently, nursing is affected by many factors that are interdependent of the concept of well-being. The physical and psychological demands of daily life can be quite challenging leading to a range of stressors, such as moral distress 3-6 …”
Section: “Nursing”mentioning
confidence: 99%